TORPEdO: A phase III trial of intensity-modulated proton beam therapy versus intensity-modulated radiotherapy for multi-toxicity reduction in oropharyngeal cancer. (January 2023) - Thomson, David J.; Cruickshank, Clare; Baines, Helen; Banner, Russell; Beasley, Matthew; Betts, Guy; Bulbeck, Helen; Charlwood, Frances; Christian, Judith; Clarke, Matthew; Donnelly, Olly; Foran, Bernadette; et al.
Highlights: There is a lack of prospective level I evidence for the use of PBT for most adult cancers including oropharyngeal squamous cell carcinoma (OPSCC). TORPEdO is the UK's first PBT clinical trial and aims to determine the benefits of PBT for OPSCC. Training and support has been provided before and during the trial to reduce variations of contouring and radiotherapy planning. There is a strong translational component within TORPEdO. Imaging and physics data along with blood, tissue collection will inform future studies in refining patient selection for IMPT.